Sustainable financing for entrepreneurs: Case study in designing a crowdfunding platform tailored for Qatar - Amna Al-Mulla; Ibrahim Ari; Muammer Koç (Digital Business, 2022)
Entrepreneurs and SMEs hold a crucial role in reaching a sustainable future by promoting decent work, innovation-driven development, and thus inequality reduction, which all fall into the UN Sustainable Development Goals. In hydrocarbon-based rentier states, however, large enterprises are drivers of economic growth by controlling the large sums of revenue from extracting, processing, and exporting oil and natural gas. Therefore, entrepreneurship in such countries encounters various obstacles, and thus, their number is very limited to foster sustainable development. Therefore, it is paramount to identify the factors that hinder entrepreneurs' and SMEs' growth. The literature shows that the fundamental barriers to financing entrepreneurship in developing countries are the lack of accessible and affordable funds, mentor support, and female participation. However, the Gulf states, particularly Qatar, are rich countries that should not experience financial deficits for entrepreneurs, and there should be underlying other reasons for discouraging entrepreneurship in those countries. This paper first identifies the fundamental problems in mobilizing domestic capital in Qatar, particularly providing funds to domestic entrepreneurs, through in-depth interviews with all the stakeholders. Second, according to the needs, this study proposes a crowdfunding platform including crowdsourcing, Entrepreneurship Majlis, to facilitate sustainable entrepreneurship by (i) exchanging ideas, (ii) providing mentorship, (iii) raising affordable funds, and (iv) supporting female entrepreneurs and investors. This platform will be easily accessible to everyone and tailored to Qatar's country-specific features, such as demography, culture, and religion. Last, the proposed platform is validated after the second round of in-depth interviews with the stakeholders.
Keywords: 650; Equity crowdfunding; Crowdsourcing; Entrepreneurship; Investor; Entrepreneur